Evolutionary approaches to the concept of drift in policy studies. Issue 2 (3rd April 2019) - Kay, Adrian; Baines, Darrin
ABSTRACT: This article is a contribution to the emerging line of scholarly inquiry into the concept of drift in the study of public policy. It investigates a persistent problem in the literature on policy drift: how to explain variation in responses to drift, separately from the process of drift itself and in order to do so how to incorporate a model of agency into the concept of drift. We argue that the broader project of evolutionary thinking in policy studies can help reveal the analytical value of an evolutionary metaphor to our understanding of policy drift. The argument is developed through a three-stage generic framework of drift in which an evolutionary metaphor helps first by assisting with accounts of the role of selection pressures in drift and, second, by supporting different accounts of agency in recognizing and responding to drift. The utility of this novel policy drift framework is illustrated through a case study of UK pharmaceutical services policy.